A pictorial review of imaging in paediatric stroke. Issue 1091 (27th June 2016) - Johns, Christopher; Kolla, S; Hart, A; Sinha, S; Batty, R; Connolly, D J A
Abstract: Stroke is recognised as an important disease in adults. Paediatric stroke is less understood, yet still an important cause of morbidity and mortality, with an incidence of 5 per 100 000 children and is one of the top 10 leading causes of death in children. In adults the vast majority of strokes are ischaemic, whereas in children haemorrhage makes up half the cases. The incidence of neonatal stroke is much higher, at up to 45 per 100 000 population; however, the underlying causes are less understood. This paper acts as a guide to the different causes of stroke with the key differences on imaging discussed.